Effect of fruit juices and chloride ions on the corrosion behavior of orthodontic archwire - Sharma M.R.; Mahato N.; Cho M.H.; Chaturvedi T.P.; Singh M.M. (My University, 2025)
Electrochemical and surface analytical study on the corrosion behavior of AISI 316L stainless steel orthodontic archwire in different fruit juices was carried out. The electrochemical parameters were measured after immersing the wires for approx. 24 h in artificial saliva (AS) containing different fruit juices and separately in fruit juices with 1% NaCl in AS. All the fruit juices used in this study increased the rate of corrosion process in AS in the presence or absence of salt. Addition of 1% NaCl to the AS, all experiments exhibited pitting. Solanum lycopersicum (Tomato) and Durio zibethinus (Amra) are rated as most detrimental to the surface followed by Prunus domestica Linn. (Plum) juice. SEM Micrographs of the specimens show formation of blisters onto the steel surface which are remnants of passive film. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.